2021
DOI: 10.1186/s12885-021-08576-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis identifies deregulated metabolic and oxidative-associated proteins in Italian intrahepatic cholangiocarcinoma patients

Abstract: Background Cholangiocarcinoma (CCA) is an aggressive disease with poor prognosis. A molecular classification based on mutational, methylation and transcriptomic features could allow identifying tailored therapies to improve CCA patient outcome. Proteomic remains partially unexplored; here, we analyzed the proteomic profile of five intrahepatic cholangiocarcinoma (ICC) derived from Italian patients undergone surgery and one normal bile duct cell line. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although citrulline was upregulated, ornithine, which is the precursor of citrulline, was downregulated by chrysanthemum extract. Previous work showed that aminoacylase-1 (3.5.1.14) was increased during oxidative stress, suggesting that chrysanthemum extract might inhibit the aminoacylase-1 and therefore cause the accumulation of N-acetylornithine and further decreases in ornithine [ 30 ]. Significantly, H 2 O 2 also decreased ornithine.…”
Section: Discussionmentioning
confidence: 99%
“…Although citrulline was upregulated, ornithine, which is the precursor of citrulline, was downregulated by chrysanthemum extract. Previous work showed that aminoacylase-1 (3.5.1.14) was increased during oxidative stress, suggesting that chrysanthemum extract might inhibit the aminoacylase-1 and therefore cause the accumulation of N-acetylornithine and further decreases in ornithine [ 30 ]. Significantly, H 2 O 2 also decreased ornithine.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical detection of ACBP/DBI also reveals high expression in cholangiocarcinoma (Cavalloni et al, 2021). ACBP/DBI mRNA levels are upregulated in non-small cell lung cancers (NSCLC), correlating with poor overall survival, cancer stage, and patient smoking history.…”
Section: Is E a S E-a Sso Ciated Alter Ati On S Of Acb P/db I In H Um...mentioning
confidence: 99%
“…Mass‐spectrometric proteomics indicates that ACBP/DBI is highly abundant in colon adenocarcinoma compared to normal tissue (Atak et al, 2018 ). Immunohistochemical detection of ACBP/DBI also reveals high expression in cholangiocarcinoma (Cavalloni et al, 2021 ). ACBP/DBI mRNA levels are upregulated in non‐small cell lung cancers (NSCLC), correlating with poor overall survival, cancer stage, and patient smoking history.…”
Section: Disease‐associated Alterations Of Acbp / ...mentioning
confidence: 99%